Evaluation of the properties of anti-corrosion coatings of steel structures - Deryushev, V. V.; Zaytseva, M. M.; Kosenko, E. E.; Mamberger, S. K. (Bezopasnostʹ tehnogennyh i prirodnyh sistem, 2020)
Introduction. The properties of an object with metal structures and the safety of its use depend on the environmental impact. This explains the urgency of the problem of universality of anticorrosive coatings. Problem Statement. The main goal of the study is to find a new approach to choosing the most rational means of protecting metal structures from corrosion based on experimental data. This takes into account the possibility of obtaining fuzzy information on various evaluation criteria. Theoretical Part. The main objectives of the study: the formation and justification of necessity of application of concepts (axioms) of sufficiency; analysis of the quality of anti-corrosion materials; constructing a measure for assessing (analyzing) the quality of facilities; evaluation (analysis) of quality of corrosion resistance in accordance with the concept of sufficiency. Conclusion. The original approach to the problem of choosing the most rational means of protecting metal structures from corrosion is based on experimental data. The considered general methodology can be used for selecting criteria for evaluating the safety of metal structures, since it is based on proven decision-making methods.